ANALYSIS OF ASPECTS OF ASSESSING THE HEALTH LEVEL OF SAVINGS AND LOAN COOPERATIVES IN KUD KARYA MUKTI KARYA HARAPAN MUKTI VILLAGE, PELEPAT ILIR DISTRICT, BUNGO REGENCY - Eryasi Daryati, (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2025)
This study aims to determine the health health level KUD Karya Mukti Unit Savings and Loans in 2016 based on the Regulation of the State Minister of Cooperatives and Small and Medium Enterprises of the Republic of Indonesia No. 14 / Per / M.KUKM / XII / 2009 concerning capital aspect, productive asset quality aspect, management aspect, efficiency aspect, liquidity aspect, independence and growth aspect, and cooperative identity aspect. This research is a type of research with qualitative approach method that is descriptive analysis. The subject of this research is the management of KUD Karya Mukti Desa Karya Harapan Mukti Pelepat Ilir District Bungo District where the object is financial aspect KUD Karya Mukti Unit Saves and Borrow Year 2016. In this research data collected through method of documentation and interview